Hearing impaired student achievement on the bahasa melayu subject : are these tests applicable? - Kamarudin, Diyana; Kamarudin, Dahlya; Hussain, Yasmin (Jurnal Pendidikan Bitara UPSI, 2019)
Hearing impairment is an area within special education. It is also one of the factors contributing to difficulty in learning at schools for children. Some students are also unable to communicate effectively with teachers. Linguistically, hearing impaired children are already having a tough time understanding the Malay subject, before adding on the two different hand codes. This study utilizes a quantitative descriptive research design where data was gathered from five schools in Malaysia, from different states. It would analyze hearing impaired student Bahasa Melayu achievement obtained from the five schools ranging from year 1 to year 6. The tests were divided into 2 sections which are comprehension and writing. Findings indicated that students did worse in their writing section compared to the comprehension section for both the mean and median analysis.